2020
DOI: 10.11591/ijphs.v9i1.20400
|View full text |Cite
|
Sign up to set email alerts
|

Medical student career choice’s determinants in Asia: a systematic review

Abstract: Asian countries have distinctive cultural patterns and norms that influence one’s decision making process throughout their life, including career choice. This review was intended to explore factors influencing medical students’ career choice in Asia. This review was compiled based on guidelines from PRISMA (Preferred Reporting Items for systematic reviews and Meta-Analysis). Data was searched and collected from studies published from electronic databases such as Pubmed, Europe PMC, Cochrane Databases, Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This implies that intrinsic motivation, despite its importance, is not the only consideration for students plans for a career in medicine. 25,30,31 According to the findings of the current study, stepwise multiple regression showed that, students' intrinsic career choice motivations were positively and significantly related to students overall 5th year cumulative GPA (B= 0.041, p<.05, CI: 0.003, 0.079), but not to their pre-clinical cumulative GPA. This study contradicts to other study which revealed that intrinsic motivation has been found to correlate with higher academic achievement in both pre-clinical and clinical years.…”
Section: Discussionmentioning
confidence: 55%
“…This implies that intrinsic motivation, despite its importance, is not the only consideration for students plans for a career in medicine. 25,30,31 According to the findings of the current study, stepwise multiple regression showed that, students' intrinsic career choice motivations were positively and significantly related to students overall 5th year cumulative GPA (B= 0.041, p<.05, CI: 0.003, 0.079), but not to their pre-clinical cumulative GPA. This study contradicts to other study which revealed that intrinsic motivation has been found to correlate with higher academic achievement in both pre-clinical and clinical years.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies show this rate can range from 2.9% to 38.2%, and it's particularly high in Asia, often exceeding 30%. 6 , 7 Notably, female medical students appear to be disproportionately affected. 7 …”
Section: Introductionmentioning
confidence: 99%